Response to the Novel Corona Virus (COVID-19) Pandemic Across Africa: Successes, Challenges, and Implications for the Future - Ogunleye, Olayinka O.; Basu, Debashis; Mueller, Debjani; Sneddon, Jacqueline; Seaton, R. Andrew; Yinka-Ogunleye, Adesola F.; Wamboga, Joshua; Miljković, Nenad; Mwita, Julius C.; Rwegerera, Godfrey Mutashambara; Massele, Amos; Patrick, Okwen; et al. (Frontiers in Pharmacology, 2020)
Background: The COVID-19 pandemic has already claimed considerable lives. There are major concerns in Africa due to existing high prevalence rates for both infectious and non-infectious diseases and limited resources in terms of personnel, beds and equipment. Alongside this, concerns that lockdown and other measures will have on prevention and management of other infectious diseases and non-communicable diseases (NCDs). NCDs are an increasing issue with rising morbidity and mortality rates. World Health Organization (WHO) warns that a lack of nets and treatment could result in up to 18 million additional cases of malaria and up to 30,000 additional deaths in sub-Saharan Africa. Objective: Document current prevalence and mortality rates from COVID-19 alongside economic and other measures to reduce its spread and impact across Africa. In addition, suggested ways forward among all key stakeholder groups. Our Approach: Contextualise the findings from a wide range of publications including internet-based publications coupled with input from senior-level personnel. Ongoing activities: Prevalence and mortality rates are currently lower in Africa than among several Western countries and the USA. This could be due to a number of factors including early instigation of lockdown and border closures, the younger age of the population, lack of robust reporting systems and as yet unidentified genetic and other factors. Innovation is accelerating to address concerns with available equipment. There are ongoing steps to address the level of misinformation and its consequences including fines. There are also ongoing initiatives across Africa to start addressing the unintended consequences of COVID-19 activities including lockdown measures and their impact on NCDs including the likely rise in mental health disorders, exacerbated by increasing stigma. Strategies include extending prescription lengths, use of drones, telemedicine and encouraging vaccination. However, these need to be accelerated to prevent increased morbidity and mortality Conclusion: There are multiple activities across Africa to reduce the spread of COVID-19 and address misinformation, which can be catastrophic, assisted by the WHO and others, which appear to be working in a number of countries. Research is ongoing to clarify the unintended consequences given ongoing concerns to guide future activities. Countries are learning from each other.